Agrarian Angst and Rural Resistance in Contemporary Southeast Asia - Rutten, Rosanne (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia, 2012)
Review of Agrarian Angst and Rural Resistance in Contemporary Southeast Asia (2009) edited by Dominique Caouette and Sarah Turner (London and New York: Routledge).